Herbicide sulfentrazone in the control of weed plants in initial posts-emergency of sugarcane crop - Teixeira Simplicio, Fernando Jose; Esposti, Clara Degli [UNESP]; Toffoli, Carlos Roberto de; Silva, Devair Goncalves da; Kuva, Marcos Antonio (Univ Estadual Centro-oeste, 2018)
Weeds negatively affect sugarcane yield, so the use of tools, such as chemical management, is essential to ensure high yields of the crop. The objective of this study was to evaluate doses of the herbicide sulfentrazone, apllied in initial post-emergence, in the control of weeds Panicum maximum, Amaranthus viridis, Digitaria horizontalis, Cyperus rotundus and Ipomoea purpurea. The experiment was carried out in a greenhouse, in a completely randomized block, with four replications. The treatments consisted of the application of sulfentrazone in increasing doses equivalent to 500, 600, 700 e 800 g i.a. ha(-1) and a control without application on the the weeds, when they were between the second and third pair of true leaves. At 3, 5, 7, 14, 21 and 28 days after application (DAA), the control was visually evaluated, and at 28 DAA the number of viable and non-viable tubers for the Cyperus rotundus species was determined. All treatments, independent of the dose, obtained results of species control percentage (above 85%), from the third day after application (DAA), for all of weeds.
Keywords: Chemical control; interference; Saccharum spp.